Support Needs of Fathers of Children with ASD: Individual, Family, Community and Ideological Influences. Issue 6 (14th July 2015) - Shave, Kassi; Lashewicz, Bonnie
Abstract : Introduction: Fathers are increasingly involved in caring for children, and involvement by fathers of children with ASD is distinctly impacted by added demands of their child's diagnosis. Yet supports for families of children with ASD are not tailored to needs of fathers. We use an ecological framework to examine how fathers' needs are influenced by contexts ranging from the immediacy of their child's behaviour to overarching expectations for good fathering. Methods: We thematically analyse data from semi‐structured interviews with 28 fathers of children with ASD who shared parenting stories of navigating their immediate and broader environments. Findings: Fathers are responsive and reflective in their parenting and value recreationally based support activities that include their children. Fathers endorse father‐to‐father support and are interested in mentoring fathers newer to the experience of having a child with ASD. Conclusions: Fathers are resourceful parents who compel a critical re‐examination towards advances in father‐friendly practices.